Gambaran Pemanfaatan Buku KIA Pada Ibu Hamil - Vinna Aurelia Widiasari; Nur Azizah Indriastuti (Universitas Malahayati Lampung, 2025)
ABSTRACT The Maternal and Child Health (KIA) Book is an important media that functions as a guide for pregnant women to monitor their pregnancy and obtain health information. However, its utilization is still not optimal due to various factors such as the mother's knowledge and attitude. This study aims to determine the description of the utilization of the KIA Book in pregnant women in the work area of the Kasihan 1 Bantul Health Center. This study uses a quantitative approach with a descriptive method. The sample consisted of 33 pregnant women who were selected by considering the theory of Baley and Mahmud and a 10% dropout risk. The instrument used was a questionnaire that had been tested for validity and reliability. Data analysis was carried out univariately and bivariately using SPSS version 26.The majority of respondents had a level of utilization of the KIA Book in the